2017
DOI: 10.17159/231-3833/1017/v47n2a3
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment for people with mental disabilities in South Africa: cost calculation of service utilisation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…30 Narrative reviews and expert opinions comprise the lowest level of scientific evidence, that is, level 5. In this study, one source by Vizzotto et al 22 is level 1, two sources by Engelbrecht et al 26 and van Niekerk et al 28 are level 2, and seven sources 13 27 31-35 are level 5. Two sources 29 36 did not specify methodology used.…”
Section: Level Of Evidence Of Included Sourcesmentioning
confidence: 58%
See 2 more Smart Citations
“…30 Narrative reviews and expert opinions comprise the lowest level of scientific evidence, that is, level 5. In this study, one source by Vizzotto et al 22 is level 1, two sources by Engelbrecht et al 26 and van Niekerk et al 28 are level 2, and seven sources 13 27 31-35 are level 5. Two sources 29 36 did not specify methodology used.…”
Section: Level Of Evidence Of Included Sourcesmentioning
confidence: 58%
“…Khare et al 29 identified the following strategies: teaching illness self-management skills, systematic involvement of families and social networks to help with job finding, collaboration on mental illness management, and facilitating work in family business. Van Niekerk et al 27 and Engelbrecht et al 26 reported similar VR intervention strategies in their studies. These were job analysis and matching, job finding, job coaching, trial placement, simulated work, work in protective factories and sheltered workshops.…”
Section: Open Accessmentioning
confidence: 81%
See 1 more Smart Citation
“…Another gap concerns the impact of adherence to fidelity in service delivery on the cost-effectiveness of programmes; good but less than perfect fidelity has been shown as most cost-effective for first-episode psychosis services [ 63 ]. Finally, another gap is the lack of economic studies in low-income countries, although costs of delivering SE/IPS have been examined in South Africa [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the budget for the health sector goes into primary health care for the purpose of preventing disease and promoting health. This lack of funding is significantly impacting the vocational rehabilitation services in SA [19] and is hindering vocational rehabilitation services that could assist people with TBIs to return to work successfully. Results of this study indicated that a lack of funding was caused by a bigger problem of a lack of legislation or the lack of practical implementation of policies to facilitate the reintegration of people with disabilities (PWD) in the workplace [20].…”
Section: Discussionmentioning
confidence: 99%